2010
DOI: 10.1016/j.ejso.2009.06.009
|View full text |Cite
|
Sign up to set email alerts
|

The lymphatic drainage of the uterine cervix in adult fresh cadavers: Anatomy and surgical implications

Abstract: Objective: To investigate the differences of the amount of paracervical lymphatic structures removed when performing classical type III, modified type II and nerve-sparing radical hysterectomy (RH). Material and Methods: Open macroscopic or laparoscopic pelvic dissections in 18 fresh adult female cadavers after lymphatic channels and nodes staining by Lipiodol dye solution injection of the uterine cervix. Results: We distinguished three different lymphatic pathways: 1) the supraureteral paracervical pathway (v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 19 publications
2
27
1
1
Order By: Relevance
“…The location of the NIR fluorescent SLNs was in concordance with formerly published drainage patterns (11). Furthermore, bilateral SLNs were found in 8 of 9 patients.…”
Section: Discussionsupporting
confidence: 87%
“…The location of the NIR fluorescent SLNs was in concordance with formerly published drainage patterns (11). Furthermore, bilateral SLNs were found in 8 of 9 patients.…”
Section: Discussionsupporting
confidence: 87%
“…Smith et al [24] reported laparoscopic skeletonisation of the uterine artery for conservative management of cervical carcinoma. In their excellent injection study using fresh cadavers, Ercoli et al [3] demonstrated the supraureteric lymphatic route along the uterine artery and superficial uterine vein plays a major and critical role in cancer metastasis from the uterine cervix. However, because of the tight entrapment of LVs close to the artery and vein, as shown in the present study, preservation of the uterine artery during complete removal of the lymphatic route would seem to be difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Using cross-sectional histology with D2-40 immunohistochemistry, we took photos at hot spots of LVs [32] in each of the sections to allow compari- Mean ± standard deviation (% in 6 mm 2 including accumulation of lymphatic vessels); 1 Along and around the uterine artery and its branches; 2 Along and around the superior vesical arteries and veins; 3 In the subperitoneal tissue in the broad ligament of the uterus; 4 In the paracolpium or paravaginal tissue 3-4 cm below the uterine cervix; 5 In smooth muscles of the bladder or ureter.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations